2020
DOI: 10.1093/cid/ciaa1280
|View full text |Cite
|
Sign up to set email alerts
|

Viral Dynamics and Immune Correlates of Coronavirus Disease 2019 (COVID-19) Severity

Abstract: Background Key knowledge gaps remain in the understanding of viral dynamics and immune response of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. Methods We evaluated these characteristics and established their association with clinical severity in a prospective observational cohort study of 100 patients with PCR-confirmed SARS-CoV-2 infection (mean age, 46 years; 56% male; 38% with comorbidities). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
166
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(191 citation statements)
references
References 38 publications
16
166
3
3
Order By: Relevance
“…In the study cohorts, a signi cant change was observed in plasma IL-6 in severe fatal cases (p = 0.0348, healthy vs. severe fatal case [early phase]; p = 0.0234, mild case vs. severe fatal case [early phase]) in line with previous studies in which IL-6 levels tended to be higher in severe cases (Fig. 3a) 14,15,24,25 . We also observed a signi cant and selective increase in IL-8 levels in the early and late phases of severe cases (p = 0.0004, healthy vs. severe surviving case [early phase]; p = 0.0002, mild vs. severe surviving case [early phase]; p = 0.0014, moderate I vs. severe surviving case [early phase]; p = 0.0001, moderate II vs. severe surviving case [early phase]; p = 0.0250, severe surviving case vs. severe fatal case [early phase]; p = 0.0388, moderate I vs. severe surviving case [late phase]; p = 0.0396, moderate II vs. severe surviving case [late phase]; Fig.…”
Section: Association Between Mdsc Subsets and Plasma Il-6 And Il-8 Lesupporting
confidence: 88%
“…In the study cohorts, a signi cant change was observed in plasma IL-6 in severe fatal cases (p = 0.0348, healthy vs. severe fatal case [early phase]; p = 0.0234, mild case vs. severe fatal case [early phase]) in line with previous studies in which IL-6 levels tended to be higher in severe cases (Fig. 3a) 14,15,24,25 . We also observed a signi cant and selective increase in IL-8 levels in the early and late phases of severe cases (p = 0.0004, healthy vs. severe surviving case [early phase]; p = 0.0002, mild vs. severe surviving case [early phase]; p = 0.0014, moderate I vs. severe surviving case [early phase]; p = 0.0001, moderate II vs. severe surviving case [early phase]; p = 0.0250, severe surviving case vs. severe fatal case [early phase]; p = 0.0388, moderate I vs. severe surviving case [late phase]; p = 0.0396, moderate II vs. severe surviving case [late phase]; Fig.…”
Section: Association Between Mdsc Subsets and Plasma Il-6 And Il-8 Lesupporting
confidence: 88%
“…The latter would be consistent with the variable antibody responses now determined for the spectrum of pediatric disease [44]. For EIA-based antibody studies otherwise, we have learned so far that the type and severity of disease and age may have bearing on the quality and quantity of antibody responses [34,[45][46][47][48]. Gender may also possibly affect antibody responses or other relevant immune responses [34,49].…”
Section: Provisional Acceptance Of What Constitutes Immunitysupporting
confidence: 64%
“…[8,9] This may be accounted by rapid con rmatory diagnosis of SARS-CoV-2 infection as the cause of pneumonia in our setting, and the vast majority of patients having non-severe infections. [10] To prepare for the pandemic, the AMS team was requested by the hospital management to work with hospital pharmacy to provide recommendations on alternative antimicrobial use in anticipation of possible shortfall. In addition, the team briefed the hospital senior management on the possibilities of antibiotic supply disruption and shared on common inappropriate use that was previously observed during audit and feedback.…”
Section: Discussionmentioning
confidence: 99%